HONESTY IN THE LEVEL OF INTERNAL CONTROL ON FINANCIAL REPORTING IN PUBLIC COMPANIES IN NIGERIA - Onah, Ewogu Boniface (PEOPLE: International Journal of Social Sciences, 2018)
This paper examined honesty in the level of internal control on financial reporting in public companies in Nigeria. It became necessary since no level of internal control is fraud free .Noticeably, public companies wine down shortly after establishment due to poor management of resources despite control measures in place. This leads to decline of public trust in accounting and reporting practices. It used a cross-sectional research design and guaranteed data through a modified 4-point likert scale questionnaire. Hypotheses formulated were tested using Z-test statistic at 5% level of significance. Among the findings were that employees (accountants) follow generally accepted accounting principles (GAAP) in reporting relevant accounting information. The audited financial statements conform to the generally Accepted Auditing principles (GAAP). Moreso, adoption and implementation of international financial reporting standard (IFRS) and international public sector accounting standard (IPSAS) have stake in comparability and reliability of financial statements. The implication is that honesty of accounting employees in the level of internal control was not compromised since it immensely improved business practices in terms of profitability, reliability and confidence of end users . It equally showed credibility and effective management functions in the firms. It therefore concludes that honesty and integrity remains vital in accounting as they bring trust. It is expected that honesty of financial reporters in financial reporting when adequately implemented in the sector will sanitize the irregularities.